ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU KEPATUHAN (COMPLIANCE BEHAVIOR) PEMBAYARAN ZAKAT PERDAGANGAN (Studi Kasus Pengusaha Muslim Batik di Kota Pekalongan Tahun 2017) - Qurotu Uyun Alpriyamah; Adityawarman Adityawarman (Diponegoro Journal of Accounting, 2017)
This study aims to analize factors that influencing zakah compliance behavior. According to the Theory of Reasoned Action (TRA) difined by Ajzen and Fisbein there are three factors likes attitude, subjective norm and intension that influencing compliance behavior. Using primary data from the questionnaires that was distributed to muslim Batik bussinessman in Pekalongan to examine their zakat compliance behavior. The data analized by multiple regression analysis using SPSS 20 for windows. The result of this study show that : (1) attitude toward behavioral intension to pay zakah is positively significant, (2) subjective norm toward intention to pay zakah is positively significant, (3) intension to pay zakah is positively significant toward zakah compliance behavior. And then (4) intension to pay zakah is significant as a mediator between the attitude and subjective norm toward zakah compliance behavior.